CHARACTERISTICS OF TRANSIT ORIENTED DEVELOPMENT AREA (CASE STUDY: JAKARTA MRT) - Siburian, Tomi Enjeri; Sumadio, Widyawati; Shidiq, Iqbal Putut Ash (UI Scholars Hub, 2020)
The city of Jakarta is famous because the traffic jams, so the transportation sector needs special attention. Based on data from the Jakarta Transportation Management Agency, of the 47.5 million trips in Jakarta City, only 24% used public transportation. The Jakarta City Government has provided public transportation modes, namely the MRT. This mode of transportation offers a basic concept of TOD, area around the 400 meter buffer from the station can be accessed by walking. This concept has been developed in various cities on the Continent of Europe and America. The space conditions in a TOD based area can be assessed using the TOD Index measurement. Each TOD Index criterion has its own indicators. This study uses 8 criteria and 18 indicators that can measure the value of the TOD Index at each MRT station. Processing data is using spatial processing so that each indicator can be analyzed holistically from a spatial perspective. The TOD area of Bendungan Hilir Station is a station with the highest TOD value, amounting to 0.71. TOD Station in Lebak Bulus Station takes the lowest TOD Index value of 0.31. The TOD Index’s value at each station can be influenced by the weight of each indicator and criteria. Through this research, it is hoped that each policyholder can pay attention to every indicator on the station that is deemed necessary to be improved if needed for a TOD-based area that is in accordance with the concept of a smart city